Temperature Distribution Pattern of Brassica chinensis during Vacuum Cooling. (28th February 2016) - Song, Xiao-yan; Liu, Bao-lin; Jaganathan, Ganesh K.
Abstract : The temperature distribution of leafy vegetables is often less uniform than that of other vegetables during the vacuum cooling process, a factor that can cause undesired effects such as frostbite. Brassica chinensis, a type of classical leafy vegetable, was used as a model in this paper to optimize vacuum cooling technology for the whole and fresh-cut leafy vegetables. We found that noticeable temperature differences between the leaf and the petiole occurred, which resulted from their structural difference. Temperature variations of different parts of the leaf were also observed, indicating that cooling rate of leaf margin was quicker than the other parts. Our experiments show that using a moderate volumetric displacement of the chamber (0.033 s −1 ) is beneficial for obtaining a relative uniform temperature distribution of the leaf part.